Oxygen anion (O−) and hydroxide anion (HO−) reactivity with a series of old and new refrigerants. (23rd February 2018) - Le Vot, Clotilde; Lemaire, Joël; Pernot, Pascal; Heninger, Michel; Mestdagh, Hélène; Louarn, Essyllt
Abstract: The reactivity of a series of commonly used halogenated compounds (trihalomethanes, chlorofluorocarbon, hydrochlorofluorocarbon, fluorocarbons, and hydrofluoroolefin) with hydroxide and oxygen anion is studied in a compact Fourier transform ion cyclotron resonance. O − is formed by dissociative electron attachment to N2 O and HO − by a further ion‐molecule reaction with ammonia. Kinetic experiments are performed by increasing duration of introduction of the studied molecule at a constant pressure. Hydroxide anion reactions mainly proceed by proton transfer for all the acidic compounds. However, nucleophilic substitution is observed for chlorinated and brominated compounds. For fluorinated compounds, a specific elimination of a neutral fluorinated alkene is observed in our results in parallel with the proton transfer reaction. Oxygen anion reacts rapidly and extensively with all compounds. Main reaction channels result from nucleophilic substitution, proton transfer, and formal H2 + transfer. We highlight the importance of transfer processes (atom or ion) in the intermediate ion‐neutral complex, explaining part of the observed reactivity and formed ions. In this paper, we present the first reactivity study of anions with HFO 1234yf. Finally, the potential of O − and HO − as chemical ionization reagents for trace analysis is discussed.